209k views
4 votes
How do I solve this using Substitution??

How do I solve this using Substitution??-example-1

2 Answers

7 votes

Answer:

-1

Explanation:

so -x-6 and x-4 are both = to y so that means they are both = to each

other so -x-6=x-4 add x to both sides -6=2x-4 add 4 to both sides 2x = -2 simplify by divide by 2 so x=-1

User BrunoLM
by
4.8k points
8 votes

Answer:

Take the second equation and add 4 to both sides, this gives you x=y+4. The plug in y+4 on the first equation, so y=-(y+4)-6, distribute the negative to everything inside the parentheses, and you get y=-y-4-6. Combine like terms and you get y=-y-10, then add y to both sides, you get 2y=-10, divide both sides by 2 and you get y=-5.

Then plug -5 into the second equation and you get -5=x-4, add 4 to both sides and you get -1=x.

If you want to check your answer, just plug in x and y to either of the equations and see if it makes a true statement.

User Sfrehse
by
4.6k points